Alburnus nasreddini, a synonym of A. escherichii (Teleostei: Leuciscidae) - Bayçelebi̇, Esra; Turan, Davut; Kaya, Cüneyt; Freyhof, Jörg (Zootaxa, 2020)
Alburnus nasreddini described from Lake Eber in Central Anatolia is a junior synonym of A. escherichii, a widespread species in adjacent Sakarya River drainage. We found no morphological characters to distinguish Alburnus nasreddini from A. escherichii and both are poorly distinguished on a molecular level also.